Air quality in Mexico City during the COVID-19 lockdown possibly decreased COPD exacerbations. Issue 4 (10th October 2022) - Montiel-Lopez, Francisco; Rodríguez-Ramírez, Daniela; Cassou-Martínez, Maricruz; Miranda-Márquez, María Cristina; González-González, Claudia; Sansores, Raúl H.; Mayar-Maya, María Eugenia; Pérez-Padilla, Rogelio; Robles-Hernández, Robinson Emmanuel; Thirion-Romero, Ireri; Pérez-Bautista, Oliver; Ramírez-Venegas, Alejandra
During the first year of the COVID-19 pandemic, various authors reported that acute exacerbations of COPD (AECOPD) were reduced [1–4]. In Mexico City, during the beginning of the pandemic, a voluntary lockdown was declared and therefore the adherence to health measures was more flexible and less stringent in the general population than in other countries [5]. However, because there was a reduction of exposure to air pollutants such as particulate matter with a diameter <10 μm (PM10 ) and <2.5 µm (PM2.5 ), as well as total suspended particles levels during the first year of the pandemic, especially among patients living in urban areas like Mexico City, AECOPD could be diminished as other countries have reported [1–4]. The reduction of air pollution during the #COVID19 lockdown in Mexico City possibly reduced the exacerbation rate in #COPD patients due to biomass and tobacco despite that the self-isolation was not as strict as expected. https://bit.ly/3Iyv98t